The genome sequence of the harlequin ladybird, Harmonia axyridis (Pallas, 1773) [version 3; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Liam M. Crowley; Douglas Boyes (Wellcome Open Research)
We present a genome assembly from an individual female Harmonia axyridis (the harlequin ladybird; Arthropoda; Insecta; Coleoptera; Coccinellidae). The genome sequence is 426 megabases in span. The majority (99.98%) of the assembly is scaffolded into 8 chromosomal pseudomolecules, with the X sex chromosome assembled.